An improved theoretical model for the maximum smoke temperature rise in a tunnel based on equivalent fire source. (April 2022) - Zhang, Shaogang; Shi, Yanli; Lin, Bin; Shi, Long; Liu, Jiahao; Wu, Yujian; Wang, Jinhui
Highlight: Maximum ceiling temperature induced by two fires is studied. Equivalent fire source of double fires is introduced. Effect of separating distance on the HRR of equivalent fire source is investigated. An improved prediction model of maximum ceiling temperature is proposed. Abstract: The maximum smoke temperature rise underneath tunnel ceiling is of great importance for the assessment of heat exposure, estimation of fire detection time and possibility analysis of fire spread. Previous studies mainly focused on the scenario with a single fire source, but the existence of two fire sources is common due to the increase traffic volume. The maximum smoke temperature rise induced by two fire sources is studied through theoretical analysis in this study. A virtual equivalent fire source is proposed, which is mainly affected by the total fire heat release rate ( HRR ) of two fires, longitudinal ventilation velocity, effective tunnel height and separating distance between two fires. The HRR of the equivalent fire source decreases with a longer separating distance, which indicates that the influences of the downstream fire on the maximum ceiling temperature weakens gradually as the separating distance increases. An improved model on the maximum ceiling smoke temperature rise caused by two fire sources was developed, and the predictions based on the revised model agree well with the experimental data.